Dietary licorice root supplementation reduces diet‐induced weight gain, lipid deposition, and hepatic steatosis in ovariectomized mice without stimulating reproductive tissues and mammary gland. Issue 2 (10th November 2015) - Madak‐Erdogan, Zeynep; Gong, Ping; Zhao, Yiru Chen; Xu, Liwen; Wrobel, Kinga U.; Hartman, James A.; Wang, Michelle; Cam, Anthony; Iwaniec, Urszula T.; Turner, Russell T.; Twaddle, Nathan C.; Doerge, Daniel R.; et al.
Abstract : Scope: We studied the impact of dietary supplementation with licorice root components on diet‐induced obesity, fat accumulation, and hepatic steatosis in ovariectomized C57BL/6 mice as a menopause model. Materials and methods: We evaluated the molecular and physiological effects of dietary licorice root administered to ovariectomized C57BL/6 mice as root powder (LRP), extracts (LRE), or isolated isoliquiritigenin (ILQ) on reproductive (uterus and mammary gland) and nonreproductive tissues important in regulating metabolism (liver, perigonadal, perirenal, mesenteric, and subcutaneous fat). Quantitative outcome measures including body weight, fat distribution (magnetic resonance imaging), food consumption, bone density and weight (Dual‐energy X‐ray absorptiometry), and gene expression were assessed by the degree of restoration to the preovariectomized health state. We characterized histological (H&E and oil red O staining) and molecular properties (expression of certain disease markers) of these tissues, and correlated these with metabolic phenotype as well as blood levels of bioactives. Conclusion: Although LRE and ILQ provided some benefit, LRP was the most effective in reducing body weight gain, overall fat deposition, liver steatosis, and expression of hepatic lipid synthesis genes following ovariectomy. Our data demonstrate that licorice root provided improvement of multiple metabolic parameters under conditions of low estrogen and high‐fat diets without stimulating reproductive tissues.